2018
DOI: 10.1088/1755-1315/126/1/012144
|View full text |Cite
|
Sign up to set email alerts
|

Potential of bacteria isolated from landfill soil in degrading low density polyethylene plastic

Abstract: Abstract. Plastic is an important material and used for many purposes. It is returned to the environment as a waste which is recently considered as the second largest solid waste. The persistency of plastic in the environment has been attracted researchers from a different point of view. The study of the degradation of plastic using bacteria isolated from local landfill soil was conducted. Low density polyethylene (LDPE) plastic was used as tested material. Potential isolates were obtained by culturing the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Four bacterial strains isolated from landfill leachate were reported to degrade Di-(2-ethylhexyl) phthalate (DEHP) in which two isolates namely LHM2 and LHM4 grew rapidly by using the pollutant as carbon source and produced biofilms [13]. Munir et al [14] reported the results of bioprospecting study of landfill bacteria in reducing the low density polyethylene plastic (LDPE) as indicated from its weight loss and bacterial cells attachment on the surface of tested material under scanning electron microscopy. Munir et al [15] again reported that the fungal isolates namely Aspergillus nomius and Trichoderma viride obtained in the same study site also displayed a high colonization on LDPE.…”
Section: Resultsmentioning
confidence: 99%
“…Four bacterial strains isolated from landfill leachate were reported to degrade Di-(2-ethylhexyl) phthalate (DEHP) in which two isolates namely LHM2 and LHM4 grew rapidly by using the pollutant as carbon source and produced biofilms [13]. Munir et al [14] reported the results of bioprospecting study of landfill bacteria in reducing the low density polyethylene plastic (LDPE) as indicated from its weight loss and bacterial cells attachment on the surface of tested material under scanning electron microscopy. Munir et al [15] again reported that the fungal isolates namely Aspergillus nomius and Trichoderma viride obtained in the same study site also displayed a high colonization on LDPE.…”
Section: Resultsmentioning
confidence: 99%
“…The plastic sheets were air-dried at room temperature for 24 h and weighed. The LDPE and LLDPE plastic sheets that showed a large change in their final weight were selected for testing at the next stage (Munir et al, 2018b).…”
Section: Biodegradation Testing With Plastic Ldpe and Lldpe Sheetsmentioning
confidence: 99%